2018
DOI: 10.1002/pssa.201800589
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Surface Relief Erasing in Amorphous As‐Se Layers: Thermal‐ and Light Induced Effects

Abstract: Here the kinetics of erasing surface relief gratings (SRGs) in amorphous As20Se80 thin films are studied under various temperatures (in the range 298–408 K) and continuous‐wave illumination by band gap light of various intensities (0–2.5 W cm−2) and polarizations. The SRGs with 3.5 and 15 μm periods and 300 nm amplitudes are recorded by two beam interference. By the measurements of erasing kinetics on the grating of two the different periods, the authors are able to separate contributions of viscous flow and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…According to our direct measurements of the viscosity coefficients in the dark and under illumination by a band gap light [24], the 'pure' viscosity coefficients practically do not depend on the illumination. Acceleration of the mass transfer under band gap illumination is caused only by the contribution of PI diffusion in the mass transfer process.…”
Section: Pi Viscositymentioning
confidence: 79%
See 4 more Smart Citations
“…According to our direct measurements of the viscosity coefficients in the dark and under illumination by a band gap light [24], the 'pure' viscosity coefficients practically do not depend on the illumination. Acceleration of the mass transfer under band gap illumination is caused only by the contribution of PI diffusion in the mass transfer process.…”
Section: Pi Viscositymentioning
confidence: 79%
“…It was found that D linearly increased with the intensity, I, and the coefficient β=D/I was equal 2.5×10 −18 m 4 /J [22]. Later, the PI diffusion coefficients were quantitavely estimated by the kinetics of growth of surface relief gratings (SRGs) at 77 and 300 K [23] for the same film composition, and recently, the PI coefficients were measured [24] in these films in a wide temperature range (308-398 K) and light intensities (0-2.5 W/cm 2 ). Using the method of capillary flattening of SRGs with two different grating periods, Λ, the authors could separate mechanisms of viscous flow (which was detected near and above glass transition temperature T g in the dark) and PI self-diffusion (at lower temperatures under band gap laser illumination).…”
Section: Basic Data On Pi Diffusion Coefficientsmentioning
confidence: 99%
See 3 more Smart Citations